On-Board Switching for Space-Integrated-Ground Information Network: Progress and Trends - Hao WU; Shuai WANG; Xiance DENG; Peilong LIU; Kai LIU; Jian YAN (天地一体化信息网络)
Considering the requirements of the space-integrated-ground information network, the technologies of on-board channelized switching and the technologies of on-board packet switching were surveyed.Among, the discussed channelized switching technologies include fl exible digital channelized switching and microwave photonic frequency conversion and switching, while the discussed packet switching technologies mainly include software-defi ned satellite network.Considering the future research directions of space networking and switching, the trends of on-board switching were discussed in terms of system capacity, reliability, effi ciency, and quality of service, which provided a reference for the long-term planning of the space-integrated-ground information network.